Hysteroscopic and ultrasonographic evaluation of ulipristal acetate treatment for symptomatic myomas in premenopausal women: a prospective study. Issue 3 (1st March 2022) - De Franciscis, Pasquale; Schiattarella, Antonio; Riemma, Gaetano; Labriola, Domenico; Ambrosio, Domenico; Vitale, Salvatore Giovanni; Cianci, Antonio; Cucinella, Gaspare; Calagna, Gloria; Colacurci, Nicola
Abstract: Objective: This study aimed to analyze the effects of a six-month therapy with ulipristal acetate (UPA) on myoma size and endometrial thickness in premenopausal women. Material and methods: Seventy-four women undergoing conservative therapy with UPA were enrolled for this study. All women underwent transvaginal ultrasound evaluation to assess the endometrial thickness, and the number and size of myomas at the beginning and after six months. Hysteroscopy and biopsy were performed after six months, if necessary. Results: After six months of treatment, sonographic examination showed a statistically significant ( p < .05) reduction of the size of the largest myoma (56.3 ± 5.1 vs. 31.7 ± 10.1 mm) and a statistically significant ( p < .05) increase in endometrial thickness (5.9 ± 2.1 vs. 9.7 ± 3.4 mm). Twenty-two patients with endometrial thickness >10 mm or nonhomogeneous pattern and ten patients with metrorrhagia underwent hysteroscopy: the most frequent finding was the combination of endometrial hypotrophy, floating surface, and chicken-wire vascular pattern aspect (14 cases, 43.7%). Histologic findings showed no case of complex hyperplasia. Conclusion: UPA is a safe, effective and assured method to decrease symptoms, reduce the need for surgery in premenopausal women suitable for the treatment.